Augmented Language Intervention and the Emergence of Symbol-Infused Joint Engagement - Adamson, Lauren B. (J Speech Lang Hear Res, 2010)
PURPOSE: This study sought to determine whether the effects of three parent-coached language interventions, two focused on augmented communication using a speech generating device and one only on speech, for toddlers with developmental delays and fewer than 10 words (Romski et al., in press) generalized to children’s joint engagement during interactions with parents that took place outside the intervention context. METHOD: Fifty-seven toddlers who participated in one of three parent-coached language interventions were observed both pre- and post-intervention interacting with their parents using a Communication Play Protocol that produced samples of communication related to social-interacting, requesting, and commenting. Their engagement states were reliably coded from the videorecords of these interactions. RESULTS: Symbol-infused joint engagement of children in all three intervention groups increased significantly from pre- to post-intervention. The amount of symbol-infused joint engagement observed post-intervention was significantly associated with whether or not the child produced spoken words and, for children in the two augmented conditions, the number of augmented words used during the last intervention session. CONCLUSIONS: The effects of parent-coached augmented language interventions generalize to children’s engagement in child-parent interactions outside the intervention context in ways that may facilitate additional language acquisition.